Book Review: Educational Research and Schooling in Rural Europe: An Engagement with Changing Patterns of Education, Space and Place - Herman Cuervo (Journal of Research in Rural Education, 2021)
In his wonderful account of rural life in Italy in the 1930s, during his exile imposed due to his antifascist activities against Mussolini's regime, the Italian writer Carlo Levi noted in his book, Christ Stopped at Eboli, "Gagliano like all Italy, was in the hands of schoolmasters" (1947/2000, p. 62). Levi, originally from Turin, offered in his experience of exile in southern rural Italy the confrontation of two cultures, his modern urban and the rural peasant way of life. Amid a rural landscape of economic hardship and poverty, and alien to the process of modernization and fascism engulfing Italy and much of Europe, Levi could not help but notice the centrality of comparaggio in the inhabitants' everyday lives"that is, an acquired and symbolic kinship, a unifying web beyond family ties, a sense of communality that brought together the people of Gagliano. Underpinning this fraternal tie was, obviously, a social history but also the centrality of the institutions of church, schooling, and agricultural work in comparison to the absence of the state.